2014
DOI: 10.1155/2014/639813
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric Properties of Aqueous Solutions of Ethylene Glycols in the Temperature Range of 293.15–318.15 K

Abstract: Densities of aqueous solutions of Ethylene glycol (EG), diethylene glycol (DEG), and triethylene glycol (TEG) were measured at temperatures from 293.15 to 318.15 K and molalities ranging from 0.0488 to 0.5288 mol⋅kg −1 . Volumes of all investigated solutions at a definite temperature were linearly dependent on the solute molality; from this dependence the partial molar volumes at infinite dilution were determined for all solutes. It was found that the partial molar volumes at infinite dilution ( 2,0 ) were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…From Table , it is detected that densities are surging with surge in concentration of EGs and are falling with surge in temperature at a certain concentration of the aniline solution. The comparison of experimental values and literature values of densities of (EG, DEG, TEG) + water is represented in Figures to and comparison for aniline + water is shown in Figure . From the figures, it is observed that the obtained density values track the same inclination as the literature values.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From Table , it is detected that densities are surging with surge in concentration of EGs and are falling with surge in temperature at a certain concentration of the aniline solution. The comparison of experimental values and literature values of densities of (EG, DEG, TEG) + water is represented in Figures to and comparison for aniline + water is shown in Figure . From the figures, it is observed that the obtained density values track the same inclination as the literature values.…”
Section: Resultsmentioning
confidence: 99%
“…Plots of experimental (filled circle) and literature values (empty square; empty triangle; star; cross; empty circle; filled diamond; empty diamond) of densities for (ethylene glycol + water) mixtures at different temperatures: red, 293.15 K; blue, 298.15 K; green, 303.15 K; brown, 308.15 K.…”
Section: Resultsmentioning
confidence: 99%
“…It is observed from Table that at a particular concentration of sorbitol, the density values of the liquid mixtures are increasing with rise in concentration of glycol and decreasing with rise in temperature. The plots of experimental data and literature data of densities of (EG, DEG, TEG) + water are shown in Figures – and the plots of experimental and literature values for density and ultrasonic velocity of sorbitol + water are shown in Figures and , respectively. It is noted from the figures that the experimental values follow the same trend as the literature values.…”
Section: Resultsmentioning
confidence: 99%
“…Plots of experimental (filled circle) and literature values (empty square; empty triangle; star; cross; empty circle; empty diamond) of densities for (ethylene glycol + water) mixtures water at different temperatures [red, 288.15 K; blue, 298.15 K; green, 308.15 K, brown, 318.15 K].…”
Section: Resultsmentioning
confidence: 99%
“…Cyclic alcohols and ethylene glycol have important industrial uses. For instance, ethylene glycol is widely used in various research such as flue gas treatment, cosmetics, antifreeze, textile, heat transfer fluid polymer precursor, petroleum, and pharmaceutical applications. When it is mixed with polar solvents, there occurs a disruption of the associated structure. Further, the presence of oxy and hydroxyl groups in the same molecule makes a versatile molecule to form intra- and intermolecular hydrogen bonds .…”
Section: Introductionmentioning
confidence: 99%